Penerapan Teknologi Dalam Pengelolaan Administrasi Keuangan Komite Sekolah Untuk Meningkatkan Transparansi Keuangan - Dyah Ayu Megawaty; Setiawansyah Setiawansyah; Debby Alita; Putri Sukma Dewi (Riau Journal of Empowerment, 2021)
Sukoharjo State Vocational High School is one of the SMK in Pringsewu Regency. This vocational school is located on Jalan Wiyata No. 107 Sukoharjo III, Sukoharjo District, Pringsewu Regency. School committee finances are obtained based on the results of committee member meetings and determine the amount to be paid by students in 1 year, in the committee member meeting it is also explained that the receipt of payments made by students can be paid in monthly installments or paid at once by students and their parents. The school committee's financial activities are carried out through the process of planning, organizing, coordinating, supervising, or controlling. Some of the financial management activities are obtaining and determining funding sources, utilization of funds, reporting, inspection, and accountability. The school committee financial information system that has been used can perform financial management in a transparent and real-time manner, so that committee members can find out the school committee's finances by utilizing information technology without having to make a financial recapitulation of the school committee to be reported to committee members or administrators.